2012
DOI: 10.1007/s13277-011-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasmatic tumor M2 pyruvate kinase and carcinoembryonic antigen in the survival of colorectal cancer patients

Abstract: Colorectal cancer (CRC) can be cured in most cases if diagnosed at an early stage. Carcinoembryonic antigen (CEA) remains the most widely used cancer marker for determining prognosis of CRC. Previous studies have shown that plasmatic tumor M2 pyruvate kinase (Tu M2-PK) is highly sensitive in CRC detection at an early stage and equally as good as the results for established tumor markers with clinical potential for cancer prognosis and monitoring. The aim of this study was to assess the prognostic value of Tu M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Fluorescent bioprobes are useful tools for optical imaging and analytical sensing, which allow direct visualization of biological macromolecules at the molecular level, facilitating the diagnosis of diseases. Recently, several lines of evidence confirmed that PKM2 had high sensitivity in the auxiliary diagnosis of various types of cancers, indicating that PKM2 has a potential application value in the early detection of cancer, prognostic judgment, and anti-tumor effect evaluation . In this study, for the first time, we designed and synthesized a novel PKM2 bioprobe by conjugating a PKM2 activator TEPP-46 with the fluorophore coumarine.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Fluorescent bioprobes are useful tools for optical imaging and analytical sensing, which allow direct visualization of biological macromolecules at the molecular level, facilitating the diagnosis of diseases. Recently, several lines of evidence confirmed that PKM2 had high sensitivity in the auxiliary diagnosis of various types of cancers, indicating that PKM2 has a potential application value in the early detection of cancer, prognostic judgment, and anti-tumor effect evaluation . In this study, for the first time, we designed and synthesized a novel PKM2 bioprobe by conjugating a PKM2 activator TEPP-46 with the fluorophore coumarine.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, several lines of evidence confirmed that PKM2 had high sensitivity in the auxiliary diagnosis of various types of cancers, indicating that PKM2 has a potential application value in the early detection of cancer, prognostic judgment, and anti-tumor effect evaluation. 38 In this study, for the first time, we designed and synthesized a novel PKM2 bioprobe by conjugating a PKM2 activator TEPP-46 with the fluorophore coumarine. This bioprobe TEPC466 was designed to induce the formation of the PKM2 tetramer and emit fluorescence via the AIE effect.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…A total of 732 patients showed a CEA-pre of <5 ng/mL, and these patients would be classified into the “normal group” according to the criteria used in previous studies ( 5 , 7 , 8 , 10 12 ). Among them, 362, 280, and 90 patients were classified into the normal, normalized, and elevated groups based on the CEA-trend classification in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Tumour pyruvate kinase M2 (M2-PK) is a key enzyme in the altered metabolism of tumour tissues. It is present in high concentrations in malignant tissues, plasma, and other body fluids 40,41 . Together with other tumour markers plasmatic and faecal levels of M2-PK could be used for prognosis.…”
Section: Colorectal Cancermentioning
confidence: 99%